A Pragmatic Analysis of Deixis in Olivia Rodrigo’s Song “Driver’s License” - Joko Prayudha.S (Program Studi Sastra Inggris Universitas Jenderal Soedirman, 2023)
Deixis is one of the pragmatic aspects that refers to words, phrases, or expressions that have different meanings depending on the contexts of who is speaking and the time and the place where the utterance is expressed. This study aims to analyze the types of deixis found in Olivia Rodrigo's song,